Optimal transform domain watermark embedding via linear programming - Pereira, S.; Voloshynoskiy, S.; Pun, T. (Signal processing, 2001)
Invisible digital watermarks have been proposed as a method for discouraging illicit copying and distribution of copyright material. In recent years, it has been recognized that embedding information in a transform domain leads to more robust watermarks. A major difficulty in watermarking in a transform domain lies in the fact that constraints on the allowable distortion at any pixel may be specified in the spatial domain. The central contribution of the paper is the proposal of an approach which takes into account spatial domain constraints in an optimal fashion. The main idea is to structure the watermark embedding as a linear programming problem in which we wish to maximize the strength of the watermark subject to a set of linear constraints on the pixel distortions as determined by a masking function. We consider the special cases of embedding in the DCT domain and wavelet domain using the Haar wavelet and Daubechies 4-tap filter in conjunction with a masking function based on a non-stationary Gaussian model, but the algorithm is applicable to any combination of transform and masking functions. Our results indicate that the proposed approach performs well against lossy compression such as JPEG and other types of filtering which do not change the geometry of the image.